The Exploration of Tactile Elements in Perfume Package Design and Their Impact on Male Consumer Purchasing Behaviors - Lin, Lung-Chi; Vongphantuset, Jirawat; Sirivesmas, Veerawat (Journal of Fine and Applied Arts Khon Kaen University, 2024)
This research highlights the underexplored role of tactile elements in perfume package design, focusing on male consumers. Men often overlook the tactile feel of a package; however, little research exists on how tactile elements of perfume packages influence this group. Furthermore, the relationship between these elements and male purchasing behavior remains largely unexplored. This study aims to achieve three objectives: 1) to explore the impact of tactile elements in perfume package design on male consumers' purchasing behavior, 2) to develop and design perfume packages specifically for men, and 3) to evaluate consumer agreement with the statements in the questionnaire regarding the designed products. Employing a mixed-methods approach, the study integrates qualitative and quantitative techniques, including in-depth interviews and questionnaires. Data from 80 participants were collected at Bangkok Design Week, February 8-12, 2023. Descriptive statistics showed that tactile elements significantly impact male consumer appeal towards perfume packages. Participants strongly concurred (average score: 4.46) on the significance of tactile features, particularly texture (4.38) and material quality (4.26). The results indicate that perfume packages with improved tactile features are well-received, evidenced by an average suitability score of 3.90. These findings provide essential insights for designers, advocating for tactile elements that align with male consumer preferences. This research addresses a gap in the literature on sensory aspects of perfume package design, offering a comprehensive understanding of its role in design and consumer behavior.